Editorial Special Issue: Urban Freight, land use planning and public administration strategies - Gatta, Valerio; Marcucci, Edoardo; Dablanc, Laetitia (REGION, 2018)
Well-being and economic growth are strictly correlated. Cities are the engines of an innovation-based economy where research and new ideas are the core input of production. Urbanisation is becoming synonymous of economic growth. People flock into cities, both in the developed and developing world, since here is where wealth is, where high quality services are available and life standards are comparatively higher with respect to other places. However, one has to acknowledge that growth also produces undesired negative effects. In fact, cities are net importers. They need to acquire consumption/intermediate goods, export production and get rid of waste. In other words, the existence of a city relies on a transportation system providing the necessary services for its functioning. The typical urban transportation system heavily depends on passenger and freight movements by road. While this dependency is, in some cases, less relevant for passenger transport, most of freight moved in, out, within and through a city relies on motorized road transportation. Trucks and vans are responsible for congestion, polluting emissions, accidents, noise, visual intrusion and stench. All these negative effects are concentrated where many citizens live and, consequently, produce relevant economic (e.g. time lost), environmental (e.g. air quality), and social (e.g. segregation) impacts. Cities to be attractive, sustainable and thriving need an efficient freight transportation system. Fast changing consumption patterns with the rise of e-commerce and home deliveries also point out to another dimension of cities: their need to adapt quickly to economic trends. The papers in this special issue address, from alternative points of view and using different methodological approaches, some of the relevant and critical issues pertaining to land use planning and administration strategies in modern cities with respect to the urban freight sector.